Will COVID “encourage” B2B and data exchange engineering in logistic firms? - Šimek Libor; Cempírek Václav (Open Engineering, 2024)
The goal of this article is to develop recommendations to assist logistic companies in formulating their B2B deployment policies as part of their engineering infrastructure strategy. It is postulated that logistic firms are likely to integrate B2B into their organizational structure in order to obtain a competitive advantage. The research examines the situation not only in the period immediately prior (2006) and after (2010) the 2008–2009 economic crisis, but also over a longer period of the following years in order to discover an eventual impact of the crisis on B2B deployment (2014, 2018). The results obtained from the 2008–2009 economic crisis are then applied analogically to the current 2020 coronavirus economic recession, where they serve as a foundation for formulating B2B deployment policy recommendations. We ascertained that B2B deployment increases in time of intensified market competition due to an economic crisis or recession and this tendency persists even in a longer horizon after the macroeconomic instability culmination. B2B systems can thus act as a significant “tool” for enhancing business competitiveness, which may be crucial for their economic “survival.”